ANALISIS KEAMANAN WEB SERVER TERHADAP WEBSITE PT. VICTORY INTERNASIONAL FUTURES MALANG DENGAN TEKNIK SQL INJECTION - Nurhayati Rumaf; Khoerul Anwar; Dwi Safiroh Utsalina (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2022)
SQL injection is an activity insert the SQL command to an existing SQL statement in the application that is running . In other words, SQL injection is a technique exploiting the web apilikasi which also uses a database for data storage . SQL injection technique allows one to log into the system without having to have an account. The method used in the analysis of web server security on the website PT.Victory International Futures with SQL Injection technique is the method of qualitative data collection through library are like a book , which contains information and theory as well as journal articles and similar studies are published on the website - the official site and reliable as supporting the completion of the study , berexplorasi in identifying weaknesses or loopholes in websites or web server that allow SQL Injection attacks. The results of the study of security analysis techniques webserver with " SQL Injection " aims to determine whether the webserver or the website is vulnerable to SQL Injection attacks , or vice versa , so that website owners can perform maintenance and repairs so that website owners be wary of internet crime.